Pemberian Vaksin Melalui Tanaman Transgenik - Radji, Maksum (UI Scholars Hub, 2004)
Vaccines have played an important role in preventive medicine since Edward Jenner discovered that cowpox induced protection against human smallpox. Until recently, a vaccination has meant a needle in the arm. However, with the increasing need for inexpensive, easily administered vaccines, along with the improvements in genetic engineering, the concept of edible vaccines is fast becoming reality. This is especially important in developing countries, where it is estimated that three to five million children die each year from common diseases, which could have easily been prevented with the proper vaccination. Compared to traditional lab-synthesized vaccines, plants are capable of producing proteins at lower cost, and need not be isolated for injection. Plant-based vaccines are also safer than traditional vaccines because they use selected sub-units of the disease rather the attenuated whole disease-causing organism.